OXYGEN COMPOUNDS OF PHOSPHORUS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
This article discusses the methodology of teaching phosphorus and its compounds using the methods of blitz survey, cluster and brainstorming.